Evaluation of the index of resistance and excretion of uromodulin in patients with predialysis CKD, taking into account the index of comorbidity - L.D. Denova (Počki, 2024)
Background. The purpose of this study was to investigate urinary uromodulin (uUMOD) excretion, reactivity of the autonomic nervous system and impaired renal blood circulation in patients with predialysis chronic kidney disease (CKD), the effect of antioxidant therapy on these parameters. Materials and methods. Ninety-one patients with CKD stage 1–5 whose average age was 47.00 ± 12.12 years took part in the ROLUNT (UROmoduLin UbiquinoNe GlutaThione) study. Thirty (32.97 %) men and 61 (67.03 %) women were divided into two groups, which were representative in terms of age and gender composition: group 1 (n = 46) — patients with CKD stage 1–5 who had a Charlson comorbidity index ≤ 2, group 2 (n = 45) — patients with CKD stage 1–5 who had a Charlson comorbidity index ≥ 3. Both groups were divided into subgroups A and B. Subgroups A included patients with impaired vegetative status, subgroups B — those without impaired vegetative status. The first A and second B subgroups took glutathione 100 mg twice a day with food for 3 months, the first B and second A subgroups took ubiquinone 100 mg once a day with food for 3 months. Results. The results of the paired t-test showed that there is a significant difference between the indicators at baseline and at the end of the study. The Pearson correlation results showed that in the group 1 (subgroup A), there is a significant average positive relationship between uUMOD and estimated glomerular filtration rate (r(21) = 0.418, p = 0.047); in the group 1 (subgroup B), there is a significant large positive relationship between uUMOD and Hb indicators (r(21) = 0.513, p = 0.012); a significant very small negative relationship between uUMOD and albumin-creatinine ratio (r(21) = 0.441, p = 0.035); in the group 2 (subgroup A), there is a significant very small negative relationship between uUMOD indicators and Kérdö  index (r(20) = 0.427, p = 0.048); in the group 2 (subgroup B), there is a significant very small negative relationship between the uUMOD indicators and Yu.M. Chernov’s questionnaire (r(21) = 0.421, p = 0.045). Conclusions. Antioxidant therapy with glutathione and ubiquinone significantly affects the examination parameters in patients with CKD. Considering the safety and effectiveness of antioxidant therapy, we suggest including it in the treatment protocols for patients with CKD. Further research is recommended to develop a standard protocol.